Analisis Faktor Intensi Berlangganan dan Keberlanjutan Pengguna Over-The-Top (OTT) Berdasarkan Teori Uses And Gratification Dengan Structural Equation Modelling - Manik, Audrey Aurelya; Aristio, Andre Parvian (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2023)
The over-the-top (OTT) video streaming platform, with all its convenience and speed, has changed the way people watch conventionally via television or cinema to use electronic devices such as smartphones or laptops. The development of digital technology and services has given birth to innovation in the world of entertainment. One of them is the behavior of watching movies. The existence of a pandemic that limits social activities and space for public movement has certainly limited people's ability to travel and seek entertainment, one of which is watching the cinema. This situation has increased the use of OTT services where people can access entertainment services such as movies, shows, news, and more from anywhere and anytime without limits using the internet network. Based on this situation, the development of OTT is also increasingly widespread and developing in providing services so that it can always satisfy user needs. One of them, OTT platform offers a subscription package so users can access all the premium services in the OTT which obviously other users don't get for free. This research aims to examine further the factors that influence purchase intensity and user continuity in subscribing to OTT services. By using a quantitative approach in the form of a questionnaire survey and testing the research model with Partial Least Square – Structural Equation Modeling (PLS-SEM) as a methodology in research focused on Use and Satisfaction, this survey research identified eight variables based on Uses and Gratification Theory for OTT use: Convenient Navigability, Binge Watching, Relaxation, Social Interaction, Friendship, Voyeurism, and Information Search. The findings of this research indicate that gratification of entertainment, companionship, and voyeurism significantly influence the intention of OTT users to subscribe. Additionally, it was observed that pricing plays a crucial role in the purchase of OTT subscription packages, as users compare the price paid with the value of content provided on the OTT platform. However, there are other factors that do not significantly impact users' intention to subscribe and continue their subscription, which need further optimization by OTT companies. The prospects of this research is that it can be a reference and scientific development for OTT service companies in observing service quality based on the factors that influence purchase intensity and user sustainability in subscribing to OTT which will later be beneficial in developing the company's strategic and managerial steps in developing its business processes.